Comparison Study of Hydrogels Properties Synthesized with Micro- and Nano- Size Bacterial Cellulose Particles Extracted from Nata de coco - Johari, NS; Ahmad, I; Halib, N (Croatian Soc Chemical Engineering Technology, 2024)
The effect of different size of bacterial cellulose particles used in the production of hydrogel was investigated. Bacterial cellulose was extracted from nata de coco, a local dessert origin from the Philippines. Micro size particle was prepared by conventional grinding of dried sheet of bacterial cellulose whereas cellulose nanoparticle was prepared by acid hydrolysis treatment. Both were then used in hydrogels formulation with acrylic acid (in ratio of 70% of bacterial cellulose dispersion to 30% acrylic acid) and exposed to electron beam irradiation (40 kGy). TEM observation showed nano cellulose particle, having range of dimension of 80 - 160 nm in length and 13 - 22 nm in diameter. It was found that hydrogel with nano cellulose has higher glass transition temperature (39 degrees C) as compared to micro cellulose hydrogel (32 degrees C). SEM observation revealed that swollen nano cellulose hydrogel has smaller and homogenous pores arrangement while micro cellulose has bigger and irregular pores thus affecting their swelling degree.